Production Management and Marketing Strategies for Enhancing Passion Fruit Syrup Sales: A Comprehensive Analysis - Resaldi Farhan; Veronica Candra; Satria Lintang Rachmadana (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2024)
The production of passion fruit syrup presents a promising business opportunity, especially given the growing consumer interest in healthy and natural beverages. Passion fruit syrup, made from fresh passion fruits, offers a unique, refreshing taste and is rich in vitamin C and antioxidants. This study, conducted as a case study on the Markisa Sunny business in Makassar, explores the production management functions, including organization, planning, control, and processing, alongside marketing strategies that focus on customer orientation, creativity, innovation, quality, and cost efficiency. The research aimed to analyze how these production management practices and marketing strategies can enhance sales. The study employed a descriptive qualitative method, with data gathered from the business owner and all employees at Markisa Sunny. The results provide insights into the production management and marketing strategies utilized by Markisa Sunny, offering practical guidance for improving product sales and business performance.